PERBANDINGAN PENAMBAHAN PELATIHAN MOBILISASI SARAF DENGAN MYOFASCIAL RELEASE PADA ACTIVE ISOLATED STRETCHING TERHADAP PENINGKATAN FLEKSIBILITAS OTOT HAMSTRING PADA MAHASISWA PROGRAM STUDI FISIOTERAPI FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Yuliartha, I Nyoman Oka; Silakarma, Dedi; Bagiada, Nyoman Agus (E-Jurnal Medika Udayana, 2017)
Flexibility is an ability of tissue or muscle for stretching to the maximum , this enables the body to move in full joint movement scope without experiencing any pain. There are occurrences in the community when the hamstring muscle flexibility was reduced. This will affect the balance of muscle contraction, posture changes, and disturbances in walking, joint stiffness, capsule and tendon disorders. To overcome this problem proper stretching is needed. The purpose of this study was to determine the difference between the training using active isolated stretching and nerve mobilization with the training using active isolated stretching and myofascial release in increasing the hamstring muscle flexibility. This research is an experiment research design with pre and post test control group design. These samples included 22 people who were divided into two groups. Group 1 was given training using active isolated stretching and nerve mobilization, while Group 2 was given the training using active isolated stretching and myofascial release. Hamstring muscle flexibility measurement was conducted through sit-and-reach test to obtain preeliminary data ISSN:2303-1395 E-JURNAL MEDIKA,VOL 6 NO 9,SEPTEMBER 2017 http://ojs.unud.ac.id/index.php/eum (before training) and final data (after training).In the Group 1 showed p = 0.000 with a mean difference 5,222±1,092, while in Group 2 showed p = 0.000 with a mean difference 4,222±1,394. The results showed there was a significant decrease in pain in each group. At different test between Group 1 and Group 2 using independent sample t-test was obtained p = 0,110 (p> 0.05). Based on these results, it can be concluded that the training using active isolated stretching and nerve mobilization showed no difference as the training using active isolated stretching and myofascial release in increasing the hamstring muscle flexibility. Keywords: Flexibility, active isolated stretching, nerve mobilization, myofascial release, sit and reach test